2012
DOI: 10.1017/s002185961200024x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in crude protein fractions of forage legumes during the spring growth and summer regrowth period

Abstract: Only a few previous studies have analysed the crude protein (CP) fractions of the Cornell Net Carbohydrate and Protein System during the growth period of forage legumes. The objective of the present study was to investigate the changes in CP fractions during the spring growth and summer-autumn regrowth period of five forage legume species (alfalfa (also known as lucerne, Medicago sativa L.), birdsfoot trefoil (Lotus corniculatus L.), kura clover (Trifolium ambiguum M.B.), red clover (Trifolium pratense L.) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 50 publications
4
33
3
1
Order By: Relevance
“…In a study by Krawutschke et al . a significant increase was observed in fraction A for red clover during the spring growth which was in contrast to our finding of no significant change.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In a study by Krawutschke et al . a significant increase was observed in fraction A for red clover during the spring growth which was in contrast to our finding of no significant change.…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies claim that the size of fraction A is not affected by plant maturity in the spring season . The discrepancy in changes in fraction A across the growing period between studies may be explained by different environmental conditions such as the supply of mineral N, water stress and soil acidity . Our data pertaining to a higher accumulation of fraction A in legumes than in grasses is supported by the study of Yu et al .…”
Section: Discussionsupporting
confidence: 84%
“…Dugalić et al (2012) reported that crude protein content in alfalfa plants ranged between 21.7% -25.9%. The nutritional value of forage crops is also influenced by stage of maturity (Krawutschke et al, 2013). Our results indicated that the highest crude protein content was measured at 150 DAS (Figure 1).…”
Section: Resultsmentioning
confidence: 65%
“…In temperate regions, white clover (Trifolium repens L.) is the predominant species used for grazing, whereas red clover (Trifolium pratense L.) and alfalfa (Medicago sativa L.) are cultivated mainly for hay and silage making (Krawutschke et al, 2013). Drought is an adverse factor that forages must cope with in the Mediterranean region.…”
Section: Introductionmentioning
confidence: 99%
“…This potential benefit has led to intensive research interest in legume protein degradability in relation to the effects of different forage species (Broderick and Albrecht, ), plant maturity (Cassida et al ., ) and genetic variation within legume species (Broderick et al ., ). There is also interest in the role of plant compounds that may enhance legume protein utilization, such as specific polyphenol oxidases (Krawutschke et al ., ) or condensed tannins (Chen et al ., ). Among a range of in vitro procedures, the Cornell Net Carbohydrate and Protein System (CNCPS) (Sniffen et al ., ) has been widely used to characterize protein degradation in forage.…”
Section: Introductionmentioning
confidence: 99%